Improving pharmacy practice in the Third World: The Jamaican experience - Mitchell, M. Faith
Using data from Jamaica, this article examines the need for more information and training in Third World pharmacies, and suggests a model of continuing education to promote informed and appropriate drug use
DOI: 10.1002/chp.4760050316
Keywords: Pharmacists